Analysis and Practice of Jiangsu Expressway Centralized Maintenance Mode. Issue 2 (April 2021) - Wang, Hongxiang
Abstract: Under the traditional maintenance mode, the contradiction between maintenance operations and traffic has negative effects on maintenance safety, efficiency, quality and benefits, and the centralized maintenance mode can effectively solve this problem. Based on the practical experience of the Jiangsu Expressway Centralized Maintenance Project, this paper summarizes the significance of carrying out the centralized maintenance of expressways, and systematically analyzes the applicability of the centralized maintenance mode from the two aspects of project requirements and external conditions. Not all expressway maintenance projects are applicable. In order to adopt the centralized maintenance mode, it is necessary to combine the construction operation content of the project and the external construction environment to make scientific decisions. Finally, taking the Shanghai-Nanjing Expressway Centralized Maintenance Project as an example, it introduces the construction organization and management characteristics of the Shanghai-Nanjing Centralized Maintenance Mode and the successful experience of the design scheme for traffic diversion of high-volume expressways, in order to provide a certain reference value for similar projects.